The role of dietary preferences in osteoarthritis: a Mendelian randomization study using genome-wide association analysis data from the UK Biobank - Chen, Long; Su, Yiqi; Li, Hui; Yang, Zhen; Li, Jiao Jiao; Xing, Dan (Frontiers in Nutrition, 2024)
Abstract Background: To understand the impact of individual preferences for specific dietary items on OA, and to help inform the development of effective and targeted OA prevention and management strategies, we performed a Mendelian randomization analysis between dietary preferences and osteoarthritis. Methods: This study utilized genetic data from the UK Biobank to investigate the association between OA and 21 different common dietary items. Instrumental variables representing European populations were carefully selected based on their genetic significance and linkage disequilibrium. In cases where a dietary item had few relevant genetic markers, a more lenient selection threshold was applied. To prevent bias, the analysis excluded single nucleotide polymorphisms (SNPs) associated with factors such as body mass index (BMI) and cholesterol. Using inverse-variance weighting (IVW) and Mendelian randomization, significant associations were detected between certain dietary items and OA. Results: Using Mendelian randomization to examine the relationship between 21 different dietary items and OA, significant associations were found for coffee, peas, watercress, and cheese, where the first two had a promoting effect and the last two an inhibiting effect on OA. Due to heterogeneity in the test results for cheese, a random IVW representation was used. The results of sensitivity analysis showed no significant heterogeneity or horizontal pleiotropy in the selected SNPS, demonstrating the reliability of Mendelian randomization analysis. Conclusion: This study identified coffee, peas, watercress, and cheese as food items that may have significant dietary effects on osteoarthritis. Mendelian randomization analysis of data from the UK Biobank revealed coffee, peas, watercress, and cheese as food items with potentially strong dietary influences on OA progression. This information may be useful to consider in the development of OA management strategies.